PERAN GURU DALAM PENERAPAN SISTEM AMONG MELALUI PROGRAM IMPLEMENTASI PEMBIASAAN 5S DI SDN 03 BLENDUNG: Sistem Among - Siti Mukhayati; Naris Setyowati; Soedjono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to identify and analyze the role of teachers in implementing the Among system through the habituation program of the 5S values (Smile, Greet, Salute, Polite, Courteous) at SDN 03 Blendung. The Among system is an educational approach emphasizing harmonious and compassionate relationships between teachers and students, fostering positive interactions within the school environment. The habituation of 5S as fundamental daily values is expected to strengthen students' character and morality by instilling positive habits that support their social and emotional development. This research employs a qualitative approach using a case study method. Data collection techniques include direct observation, in-depth interviews with teachers and students, as well as documentation related to program implementation in the school. The findings reveal that teachers at SDN 03 Blendung play a pivotal role in implementing the Among system through the 5S habituation program. Teachers act not only as educators but also as role models in practicing the 5S values in daily life, both inside and outside the classroom. The 5S program not only shapes students' better character but also creates a more conducive, harmonious, and respectful school atmosphere. Overall, this study concludes that the role of teachers in implementing the Among system through the 5S habituation program at SDN 03 Blendung is crucial for creating an environment that supports students' character development. The study also recommends that similar programs be expanded and adapted in other schools to support character building among students across Indonesia.